Sustainability analysis for irrigation water management in the Aral Sea region - Cai, Ximing; McKinney, Daene C.; Rosegrant, Mark W. (Elsevier, 2003)
Sustainable irrigation water management should simultaneously achieve two objectives: sustaining irrigated agriculture for food security and preserving the associated natural environment. A stable relationship should be maintained between these two objectives now and in the future, while potential conflicts between these objectives should be mitigated through appropriate irrigation practices. Lessons learned from unsustainable water management practices around the world demonstrate the necessity—and growing urgency—of applying sustainability principles to water management in river basins where irrigation is a major factor. This article presents the operational concepts and analytical framework for sustainability analysis of irrigation water management in irrigation-dominated river basins. These are applied to the Aral Sea region in Central Asia, a region famous for its conflict between sustaining irrigated agriculture and preserving the environment.